Table of Content - - (Journal of natural sciences, life and applied sciences, 2023)
Table of Content 1. Natural factors and their impact on human security Dr. Salwa Hassan Ahmed 2. The effects of climate change on water resources in north-eastern Morocco, the case of Berkane city Dr. Mustapha Benasquar, Dr. Abdel Khalek Ghazi , Mr. Abdel Wahed Ahroud, Mr. Noureddine Buabid1 3. Afforestation targets according to remote sensing techniques and geographic information systems in Imam Turki bin Abdullah Royal Natural Reserve Prof. Ahmed Abdullah Al-Dughairi 4. The Effects of the Alternative Electrical Generators on Air, applied on Gaza City Dr. Hala Rezeq Al-Harazin 5. The morphometric analysis of Al Nisr Valley Basin in Al Mithnab Governorate, in Kingdom of Saudi Arabia, using remote sensing and the Geographic Information System Dr. Wedad Hammdan Al-Ruqi 6. Runoff hydrographs using Snyder and SCS synthetic unit hydrograph methods: A case study of ungauged watersheds of Imam Turki Bin Abdullah Royal Nature Reserve (ITBA) - Saudi Arabia Prof. Ahmed Abdullah Al-Dughairi